Beak trimming methods and their effect on the performance and egg quality of Japanese quails (Coturnix japonica) during lay - Pizzolante, C. C.; Garcia, Edivaldo Antonio [UNESP]; Salclanha, E. S. P. B.; Lagana, C.; Faitarone, A. B. G. [UNESP]; Souza, H. B. A. [UNESP]; Pelicia, K. (Facta-fundacio Arnco Ciência Tecnologia Avicolas, 2007)
A total number of 720 Japanese quail females, reared under identical management conditions, and receiving feed and water ad libitum, was used. Quails were housed and reared from 1-35 days of age in litter pens in a rearing house, and then were transferred to a quail layer house. This study aimed at verifying if different beak trimming method could optimize egg production and quality by reducing stress and cannibalism among birds. A completely randomized experimental design was used, with six treatments in a 2x3 factorial arrangement, with two beak trimming ages (14 and 21 days) and three beak trimming variants (non-trimmed, 1/3 of the beak trimmed, or 1/2 of the beak trimmed), 6 replicates of 20 birds each. Performance was evaluated by feed intake, percentage of lay, egg mass, feed conversion ratio per dozen and per kg eggs, and mortality. Performance was influenced by trimming variant, with the best results obtained by birds with intact and those with 1/3 of the beak trimmed. Better specific gravity was in quails submitted to beak trimming at 21 days of age, whereas other egg quality parameters did not present significant results. Based the results obtained in the present study, it is recommended to submit to beak trimming either at 14 or 21 days of age.
Keywords: age; beak trimming; feathering; performance; quails